تقييم الأداء المالي لمؤسسات التأمين بالجزائر بإستخدام النسب المالية دراسة حالة مؤسسة أليانس للتأمينات -أنموذجا- من الفترة الممتدة 2015-2021 - بوجمعة ياسين; غربي خليل (جامعة الوادي University Of Eloued, 2024)
تهدف الدراسة إلى معرفة أهمية النسب المالية في تحليل الأداء المالي لمؤسسة أليانس خلال الفترة من عام 2015 إلى 2021، كما يهدف البحث أيضاً إلى تقييم الوضع المالي للمؤسسة وكشف مستوى أدائها المالي خلال الفترة المعنية، تم استخدام مؤشرات مالية محددة لتحليل القوائم المالية، وقد أظهرت النتائج تراجعًا في الأداء المالي لمؤسسة أليانس، وذلك استنادًا إلى التحليل المالي، وعليه يمكن استنتاج أنها تتطلب اتخاذ قرارات مالية استباقية لتحسين وضعها المالي وتحسين أدائها. The study aims to know the importance of financial ratios in analyzing the financial performance of the Alliance Foundation during the period from 2015 to 2021. The research also aims to evaluate the financial situation of the institution and reveal the level of its financial performance during the relevant period. Specific financial indicators were used to analyze the financial statements, and the results showed A decline in the financial performance of Alliance, based on the financial analysis, and therefore it can be concluded that it requires taking proactive financial decisions to improve its financial position and improve its performance.
Evaluating the financial performance of insuranceinstitutions in Algeria using financial ratios Case study of Alliance Insurance -a model - from the period 2015-2021
Keywords: الأداء المالي; النسب المالية; مؤسسة أليانس; Financial performance; financial ratios; Alliance Foundation